Challenges to the Development of a Flipped Classroom in Grade 6 Geography - Mokoena, Matome Joseph; Khoza, Samuel Dumazi; Skosana, Ndlelehle Miskien (The Asian Journal of Technology Management (AJTM), 2025)
Abstract. This qualitative study explores the challenges facing efforts to develop a flipped classroom in grade 6 geography classes at a school district in North West Province, South Africa. This research was conducted because the current instructional practices in these classes leave much to be desired, encouraging passive learning among students. Data was collected, following purposive sampling, from five grade 6 geography teachers and five department heads through face-to-face interviews and, later, non-participant classroom observations with the teachers. The findings reveal that, although teachers are keen on integrating information and communications technology in their classrooms, they lack the necessary digital tools. This problem is exacerbated by their shallow technology skills, which hinder their efforts to flip the classroom. Even though learners are typically digitally savvy, contextual factors prevent them from learning independently through digital means, leaving them with a passive learning approach. Ultimately, the study recommends, among other proposals, that teachers be trained to use ICT and digital tools so as to facilitate digitally enabled classrooms. Keywords: Flipped classroom, information and communications technology, geography, technological and pedagogical content knowledge